2006
DOI: 10.1074/jbc.m607892200
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Perlecan Enhances Collagen Fibril Formation

Abstract: Inactivation of the perlecan gene leads to perinatal lethal chondrodysplasia. The similarity to the phenotypes of the Col2A1 knock-out and the disproportionate micromelia mutation suggests perlecan involvement in cartilage collagen matrix assembly. We now present a mechanism for the defect in collagen type II fibril assembly by perlecan-null chondrocytes. Cartilage perlecan is a heparin sulfate or a mixed heparan sulfate/chondroitin sulfate proteoglycan. The latter form binds collagen and accelerates fibril fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 48 publications
4
69
1
Order By: Relevance
“…Also, the concentration of Col I affects strongly fibril formation as found previously [40,41]. Presumably CS binds to collagen molecules and facilitates the organization of mature fibrils by increasing collagen concentration as it was found in the presence of 4,6-disulfated disaccharides structures, previously [38]. In line with this, here a pronounced fibril formation in both nCS and oCS-based PEMs was observed, when more Col I was adsorbed, which showed also a specific network-like organization as in connective tissue.…”
Section: Physicochemical Characterization Of Polyelectrolyte Multilaysupporting
confidence: 66%
See 1 more Smart Citation
“…Also, the concentration of Col I affects strongly fibril formation as found previously [40,41]. Presumably CS binds to collagen molecules and facilitates the organization of mature fibrils by increasing collagen concentration as it was found in the presence of 4,6-disulfated disaccharides structures, previously [38]. In line with this, here a pronounced fibril formation in both nCS and oCS-based PEMs was observed, when more Col I was adsorbed, which showed also a specific network-like organization as in connective tissue.…”
Section: Physicochemical Characterization Of Polyelectrolyte Multilaysupporting
confidence: 66%
“…Conversely, rather sparse and short fibrils were observed in both nHA and oHA-containing PEMs, where Col I seemed to form rather discrete aggregates than fibers. Col I fibrillogenesis is a sophisticated process highly affected by environmental factors, such as pH, electrolyte type and collagen concentration, but also on the presence of GAG like CS and other naturally occurring polyanions [37,38]. In general, at pH value <5.5 Col I forms more globular structures, while at pH value >5.5 normally fibrillogenesis is supported [39].…”
Section: Physicochemical Characterization Of Polyelectrolyte Multilaymentioning
confidence: 99%
“…More recently, it has been shown that the chondroitin sulfate side chains of perlecan, but not its heparan sulfate chains, will promote collagen fibrillogenesis in vitro. These chondroitin sulfate chains differ from those found on aggrecan, which are inert with regard to fibrillogenesis and essentially lack the incorporation of chondroitin sulfate E type oversulfated disaccharides (25) as found in perlecan chondroitin sulfate chains.…”
mentioning
confidence: 77%
“…Collagen Fibrillogenesis Assay-The assays were performed as described previously (29). Pepsin-extracted acid-solubilized collagen (Vitrogen) was neutralized and diluted (167 pM) in 150 mM NaCl, 20 mM HEPES, pH 7.4, with decorin or mutated decorins at 4°C.…”
Section: Methodsmentioning
confidence: 99%